UPAYA PENINGKATAN PEMBELAJARAN LITERASI SAINS DAN STEAM BAGI GURU-GURU TK DI DESA BARU SIAK HULU - Raihana, Raihana; Alucyana; Harahap, Musaddad; Rofiatin, Siti; Siregar, Rukia; Utama, Ferdian; Dea, Leli Fertiliana (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract The low level of scientific literacy and critical thinking does not only occur in PAUD students, especially Kindergarten, but also occurs in Kindergarten teachers, this causes less than optimal learning in Kindergarten, especially in STEAM learning. In fact, to overcome the low level of scientific literacy, the government has included STEAM literacy and learning in the independent PAUD curriculum, which is one of the government's priority programs through the Ministry of Education and Culture, but in the field there are still many kindergarten teachers who do not know scientific literacy and STEAM learning, even though teachers are at the end of the scale. spear in a lesson. This Community Service is carried out with the aim of providing additional knowledge to kindergarten teachers regarding scientific literacy and STEAM learning. The method used in PkM uses a community approach, the community in question is the kindergarten teachers in Baru village, totaling 15 people consisting of 3 kindergartens. The implementation of PkM uses lectures as a model for delivering the material. The results of implementing this PkM are that kindergarten teachers gain new knowledge, skills and creativity in terms of scientific literacy and STEAM learning.